Arabic Teacher Pedagogic Competence in Managing Learning at Madrasah Aliyah Negeri 1 bandar lampung|Al Kafa’ah At Tarbawiyyah Li Mu’alim Al Lughoh Al ‘Arobiyyah Fii Idaaroti At Ta’liim Bimadrosah Al ‘Aaliyah Al Islamiiyah Al Hukuumiyyah Al Ulaa Bandar Lampung: الكفاءة التربوية لمعلم اللغة العربية في إدارة التعليم بمدرسة العالية الإسلامية الحكومية الأولى بندار لامبونج - Saiful Anwar; Umi Hijriyyah; Zulhanan; Erlina; Muhamad Rizki Murtadho; Mu'min Nasirul Haq (Mantiqu Tayr: Journal of Arabic Language, 2023)
The objective of this study was to know the teachers’ pedagogic competence to manage the teaching and learning Arabic language at Madrasah Aliyah Negeri 1 Bandar Lampung in designing plans, implementing and evaluating learning. The research methods of the study is descriptive qualitative. Data were collected through observation, interview, and documentation. The data analysis procedure uses several steps, namely data reduction, data presentation and verification. The result of data findings shows that the teachers’ pedagogic competence to manage the teaching and learning of Arabic teachers in planning, implementation dan evaluation learning is good. the teacher plans learning by: a) Understanding the characteristics of students. b) The preparation of the Learning Program as a result of the lesson plan is a very important thing for a teacher to do. Then in carrying out learning by: a) Opening Learning; b) Do Apperception; c) Perform Pre Test; d) Delivering Study Material; e) Using the Method; f) Using the Media; g) Class management; h) Closing Learning. And in carrying out learning evaluations, carrying out daily assessments such as giving practice questions after one material has been studied. In addition, there are UTS and UAS in one semester. Overall the teacher's pedagogical competence in managing learning is in the good category.